Effect of Compost Dosing on the Growth of Nyatoh (Palaquium sp) Seedlings in the Nursery - Muchtar, Asikin; Muib, Renpius; Herawati , Herawati (Jurnal Wasian, 2024)
The growth of Nyatoh (Palaquim sp) seedlings is very slow so they need to be given treatment to speed up their growth in the field. Nyatoh (Palaquim sp) seeds are endemic to South Sulawesi and make good quality wood for house building materials. This research aims to determine and analyze the interaction of giving compost fertilizer on the growth of Nyatoh (Palaquium sp) seedlings in the nursery, as well as knowing and analyzing the appropriate dosage according to the growth needs of Nyatoh (Palaquium spp) seedlings in the nursery. The research method used was an experimental method with 3 repetitions. Nyatoh seeds which are available in the form of polybags are approximately 2 months old in the nursery, then seeds with a uniform height of around 15 cm are selected for a total of 90 seedlings. Next, compost fertilizer is prepared from fermented cow dung, then weighed at a dose of 30 gr/seed coded (P1), 40 gr/seed (P2), and 50 gr/seed (P3). Initial growth measurements (first week) were carried out when the seeds were mixed with compost for each Nyatoh seedling. Then the next measurement was carried out in the 4th week (final measurement) on 90 Nyatoh seedlings in the nursery.The results of the research showed that the interaction of giving compost fertilizer to Nyatoh seedlings had a very significant effect on the increase in height and number of leaves of Nyatoh seedlings in the nursery, with a calculated F value of 14,955 > F table value of 4,459 and F calculated 12,043 > 4,459. The treatment of providing compost fertilizer at a dose of 40 gr/seed (P2) had a very significant effect on the increase in height and increase in the number of leaves of Nyatoh seedlings in the nursery.